Pesan Al Quran dalam Kerjasama Musa dengan Syu'ayb tentang Pengelolaan Bisnis - Alimin Mesra (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
Prophet Moses and Prophet Syu'ayb companion ultimately led them to work together. This case reveals a number of values that should be developed and applied in life related to business management. This story reveals a relation between employees and owners of capitla, recruitment patterns, appreciation of performance, proffesionalism, and some related matters. The cooperation between them can be considered as a symbolic learning delivered by the Quran, especially in business development. This story also shows that a partnership should be based on a clear contract that shows such related materials, working period, the amount of wages, security, and others related to their right and obligation. DOI: <span style="color: #222222; font-family: arial, sans-serif; font-size: 12.8px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline !important; float: none; background-color: #ffffff;">10.15408/aiq.v4i1.2080